Pengembangan Perangkat Lunak Untuk Analisis Aliran Beban Tiga Fasa Pada Jaringan Tegangan Rendah Dengan Metode Newton Berbasis Calculus Wirtinger - Harifin, Hayatul; Daratha, Novalio; Rosa, M. Khairul Amri (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2020)
AbstractLoad flow analysis is a study to plan and determine the amount of power in an electric power system. During its development, industry requires a large amount of electric power and uses electrical equipment as a means of production. The benefits of an electric load flow analysis are to find out the amount of power in the electric power system whether it still meets predetermined limits, and to find out the amount of voltage at each point, and to obtain initial conditions for the new system planning. Load flow analysis begins calculating the active power and reactive power at each node (bus) installed, loading on the channel or conductor, the load flow calculation will be assisted using the Julia program. From the results of calculations using the Julia program, the voltage at each point with the smallest stress is obtained, namely the 10th point of 209.89 - j10.34V for phase A, -107.39 - j186.87V for phase B, -108.12 + j178,51V for phase CKey Words: Drop Voltage, Julia, Load Flow